2023
DOI: 10.4014/jmb.2308.08046
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Hemoprotein Diet Changes Adipose Tissue Distributions and Re-Shapes Gut Microbiota in High-Fat Diet-Induced Obese Mice

Seungki Lee,
Ahyoung Choi,
Kyung-Hoon Park
et al.

Abstract: We have previously observed that feeding with single-cell hemoprotein (heme-SCP) in dogs (1 g/day for 6 days) and broiler chickens (1 ppm for 32 days) increased the proportion of lactic acid bacteria in the gut while reducing their body weights by approximately 1~2%. To define the roles of heme-SCP in modulating body weight and gut microbiota, obese C57BL/6N mice were administered varied heme-SCP concentrations (0, 0.05, and 0.5% heme-SCP in high fat diet) for 28 days. The heme-SCP diet seemed to restrain weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Notably, reductions in T-chol and LDL-c showed large effect sizes with absolute d values of over 0.8 (Table 1 ). Although we could not make a conclusive discussion due to the small number of replicates ( n = 3), the outcomes correspond with the previous study [ 33 ]. Therefore, C. glutamicum heme-SCP can be a valuable alternative hemoprotein for supplying heme iron.…”
Section: Resultssupporting
confidence: 46%
See 1 more Smart Citation
“…Notably, reductions in T-chol and LDL-c showed large effect sizes with absolute d values of over 0.8 (Table 1 ). Although we could not make a conclusive discussion due to the small number of replicates ( n = 3), the outcomes correspond with the previous study [ 33 ]. Therefore, C. glutamicum heme-SCP can be a valuable alternative hemoprotein for supplying heme iron.…”
Section: Resultssupporting
confidence: 46%
“…Corynebacterium glutamicum , classified for Qualified Presumption of Safety (QPS) or Generally Recognized as Safe (GRAS) microorganism, can biosynthesize hemoproteins [ 29 31 ]. Previous studies have revealed that C. glutamicum heme-SCP has health benefits by positively influencing intestinal microbiota and blood fat levels in pet dog or obese mouse models [ 32 , 33 ]. Hemoproteins in C. glutamicum contribute to microbial growth and resistance against oxidative stress.…”
Section: Introductionmentioning
confidence: 99%